Dead at daybreak eaudiobook - Meyer, Deon (HighBridge Audio, 2012)
An antiques dealer robbed and killed, and the only clues are a scrap of blank paper and the unusual weapon used. Now ex-cop Zatopek 'Zed' van Heerden has fourteen days in which to fill in the blanks in this dead man's past-a past which only seems to begin in 1983.